An introduction to the study of Luke-Acts - Shillington, V. George (London, UK T. and T. Clark, 2007)
Contents : Luke-Acts: an aerial view -- Historical enquiry: composition, context and intention -- Historical enquiry: events and people inside the text -- Social-science scenarios: where people live and think -- Socio-rhetorical texture: membership in the new people of God -- Narrative discourse: poor and rich in Christian community -- Postcolonial engagement: missionary attitude and activity -- Feminist praxis: "both men and women" -- Theological interchange: "saying to one another". Includes bibliographical references and indexes.
Keywords: Bible. N.T. Luke -- introductions; Bible N.T. Luke -- criticism, interpretation, etc; Bible. N.T. Acts -- introductions; Bible. N.T. Acts -- criticism, interpretation, etc